6-2x=5x-9x+10-4

Simple and best practice solution for 6-2x=5x-9x+10-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-2x=5x-9x+10-4 equation:


Simplifying
6 + -2x = 5x + -9x + 10 + -4

Reorder the terms:
6 + -2x = 10 + -4 + 5x + -9x

Combine like terms: 10 + -4 = 6
6 + -2x = 6 + 5x + -9x

Combine like terms: 5x + -9x = -4x
6 + -2x = 6 + -4x

Add '-6' to each side of the equation.
6 + -6 + -2x = 6 + -6 + -4x

Combine like terms: 6 + -6 = 0
0 + -2x = 6 + -6 + -4x
-2x = 6 + -6 + -4x

Combine like terms: 6 + -6 = 0
-2x = 0 + -4x
-2x = -4x

Solving
-2x = -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-2x + 4x = -4x + 4x

Combine like terms: -2x + 4x = 2x
2x = -4x + 4x

Combine like terms: -4x + 4x = 0
2x = 0

Divide each side by '2'.
x = 0

Simplifying
x = 0

See similar equations:

| 3*p-5=2p | | 29x+11y=-17-29x | | 3y^2+22y-16=0 | | 5x+9+6=-9 | | m^6-n^6=0 | | x^6-35x^3+216=0 | | -3*2n+5=-9 | | 2v^3-3v^2-4v+6=0 | | 80+6x=145-7x | | (x-12)+(2x-8)=13 | | 9x^2-167x+612=0 | | 6c-1=-2 | | 5-7(2n+1)= | | 3+7x=3x-33 | | 18x^3+39x^2+20x=0 | | L=2(4.5)+3 | | (y-2)(y-2)=2y^2+2y+13 | | 3x+-6=7-2x | | 3(x-7)+2(x+5)=27 | | 20x+25=85 | | (4x^2-5)(3x^2+7)=0 | | 100x=2 | | (W^2)-3w=-3 | | .05z+.1(2z)+.25(100-3z)=20 | | 3x+5=83 | | 1+1u=5 | | 23x-2+2x=56 | | 2x^2=23x+39 | | -84x-96=-18x+60 | | 7p-3=-17 | | x^2=-50 | | 10v^5-32v^4+6v^3=0 |

Equations solver categories